Thanatin and vinyl sulfide analogues as narrow spectrum antimicrobial peptides that synergise with polymyxin B - Shepperson, Oscar A.; Harris, Paul W. R.; Brimble, Margaret A.; Cameron, Alan J. (Frontiers in Pharmacology, 2024)
Thanatin is a β-hairpin antimicrobial peptide cyclised by a single disulfide bond that has shown potent broad-spectrum activity towards bacterial and fungal pathogens. Towards Gram-negative species, thanatin acts both by forming trans-membranal pores and inhibiting outer membrane biogenesis by binding to LptA and blocking lipopolysaccharide (LPS) transport. Inspired by previous modifications of thanatin, an analogue was prepared which demonstrated potent but selective activity towards E. coli. Furthermore, this compound was shown to act in synergy with the highly potent FDA-approved lipopeptide antibiotic polymyxin B, which engages LPS at the cytoplasmic membrane. Four analogues of thanatin in which the disulfide was substituted for vinyl sulfide bridge mimetics were prepared, all of which retained similar secondary structures. Two of these retained substantial potency and selectivity towards E. coli. Importantly, synergy with polymyxin B was also maintained for the lead analogue. The vinyl sulfide potentially offers a facile replacement strategy for labile disulfide bonds and the selective activity and drug synergy of the reported thanatin analogues is promising for the development of narrow spectrum antimicrobials with reduced likelihood of resistance emerging in clinical settings.